2017
DOI: 10.1016/j.cub.2017.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Profilin Directly Promotes Microtubule Growth through Residues Mutated in Amyotrophic Lateral Sclerosis

Abstract: SUMMARY Profilin is an abundant actin monomer binding protein with critical actin regulatory roles in vivo [1,2]. However, Profilin also influences microtubule dynamics in cells, which may be mediated in part through its interactions with Formins that in turn bind microtubules [3,4]. Specific residues on human Profilin-1 (PFN1) are mutated in patients with amyotrophic lateral sclerosis (ALS) [5,6]. However, the observation that some ALS-linked PFN1 mutants fail to alter cellular actin organization or dynamics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
94
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 70 publications
(99 citation statements)
references
References 44 publications
5
94
0
Order By: Relevance
“…As referred to above, the effect of Pfn1 in promoting microtubule growth rates in vitro and in neuroblastoma cells contrast with data obtained in melanoma cells (Nejedla et al, ). Surprisingly, when Pfn1 was depleted from N2A cells, an increased microtubule growth speed was also obtained, although to a smaller extent than that produced by Pfn1 overexpression (Henty‐Ridilla et al, ). It was therefore concluded that microtubule growth rates are probably highly sensitive to Pfn1 levels in either direction, although no mechanism has been put forward to explain this apparent discrepancy.…”
Section: Profilin Interferes With Microtubule Dynamics: Direct Versusmentioning
confidence: 94%
See 4 more Smart Citations
“…As referred to above, the effect of Pfn1 in promoting microtubule growth rates in vitro and in neuroblastoma cells contrast with data obtained in melanoma cells (Nejedla et al, ). Surprisingly, when Pfn1 was depleted from N2A cells, an increased microtubule growth speed was also obtained, although to a smaller extent than that produced by Pfn1 overexpression (Henty‐Ridilla et al, ). It was therefore concluded that microtubule growth rates are probably highly sensitive to Pfn1 levels in either direction, although no mechanism has been put forward to explain this apparent discrepancy.…”
Section: Profilin Interferes With Microtubule Dynamics: Direct Versusmentioning
confidence: 94%
“…To test the biological relevance of the observations made in vitro, Pfn1 was overexpressed in mouse neuroblastoma (N2A) cells. By tracking microtubule (+)‐ends, microtubule growth speed was increased by almost threefold and a significant increase in microtubule entry into filopodia was also observed (Henty‐Ridilla et al, ). As referred to above, the effect of Pfn1 in promoting microtubule growth rates in vitro and in neuroblastoma cells contrast with data obtained in melanoma cells (Nejedla et al, ).…”
Section: Profilin Interferes With Microtubule Dynamics: Direct Versusmentioning
confidence: 94%
See 3 more Smart Citations